Herd Behaviour in the Cryptocurrency Market: Fundamental vs. Spurious Herding - Senarathne, Chamil Wansaja; Jianguo, Wei (The European Journal of Applied Economics, 2020)
This paper sets out to explore whether the investor herding in the cryptocurrency market induces correlations in cryptocurrency returns using the methodologies of Chang, et al, (2000) and Galariotis, et al. (2015) from a daily data sampling period of 3/30/2015 to 5/24/2019. The initial regression results show that the CSAD can only be explained by GSCI oil and gold index return and no relationship exists between CSAD and other regression variables such as return on CCi30, US equity risk premium and US/Euro exchange rate return. The herding regression under normal market condition (i.e. general market conditions) shows that there exists a strong tendency to herd on non-fundamental information that explains CSAD of returns, indicating the speculative nature of cryptocurrency price changes. As such, cryptocurrency returns cannot be predicted on the basis of fundamental economic information (e.g., major macroeconomic announcements). Herding on non-fundamental information is found to be more pronounced during up markets and other than up market periods. No signs of herding on fundamental information could be observed under any other market conditions. These findings provide guidance for portfolio managers who could benefit from portfolio diversifications by investing in the cryptocurrency market and hedge the pricing risk against various other classes of speculative assets whose prices largely move (i.e. change) based on fundamental information. As such, cryptocurrency exchange is shown to provide a more efficient trading platform for investors.